Influence Return on Assets, Cash Turnover and Receivable Turnover Against Liquidity of Automotive Companies Listed on the Indonesia Stock Exchange - Rizka Alamsaputri; Zulkifli Zulkifli (Cita konsultindo, 2023)
This research aims for know and analyze influence return on assets, cash turnover and receivable turnover to liquidity company. Population this research is company automotive listed on the Indonesia Stock Exchange. Retrieval technique sample use purposive sampling with determination criterion, that is company Consistent automotive recorded in accordance period observation For done analysis in research . Types of research data with secondary data which method collection using report data auditing finance. Method data analysis with analysis panel data regression. The results of this study determine the best model, ie fixed effect and proven that return on assets own influence negative and significant to liquidity company. Whereas cash turnover and receivable turnover No influential significant to liquidity company.